PENGEMBANGAN MEDIA WEB FLIPBOOK BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI KEBERAGAMAN BUDAYA DI PROVINSI JAWA TIMUR BAGI SISWA KELAS V SDN PLOSO - Fatma Debriliya, Ica; Saidah, Karimatus; Ibnu Zaman, Wahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop augmented reality (AR)-based flipbook web media to improve the learning outcomes of fifth grade students of SDN Ploso on the material of cultural diversity in East Java. The background of the research is the low interest and learning outcomes of students due to conventional learning and minimal media. The method used is the ADDIE development model with the stages of analysis, design, development, implementation, and evaluation. The instruments used include validation questionnaires, practicality questionnaires, and learning outcomes tests. The results showed that the media was declared very valid (89.09% of media experts and 96% of material experts), very practical (86.67% of teachers and 91.43% of students), and effective in improving learning outcomes (post-test score 95.75%). This media is suitable for use as an innovative learning alternative based on the Merdeka Curriculum.